Analisa Pengetahuan, Kepatuhan dan Pengendalian Terhadap Pencegahan Covid 19 pada Masa Transisi Endemi di Institut Teknologi Petroelum Balongan Indramayu - Rien Herdiyani (Syntax Idea)
COVID-19, also known as Coronavirus Disease, is a new type of infectious disease discovered in 2019 that has become a global pandemic (WHO, 2020). The first cases were identified in Wuhan, Hubei Province, China, with reports of unexplained cases of pneumonia. On January 30, 2020, the Director-General of the WHO declared the COVID-19 outbreak a Public Health Emergency of International Concern. The aim of this research is to comprehensively analyze Knowledge, Compliance, and Control in Preventing COVID-19 during the Endemic Transition Period at the Balongan Institute of Petroleum Technology in Indramayu. The research method employed for this study was a survey, involving the distribution of questionnaires to 114 employee respondents. Data analysis was conducted using Structural Equation Modeling (SEM). The conclusions drawn from this study are as follows: There is an influence of knowledge about COVID-19 on compliance and COVID-19 prevention. However, knowledge about COVID-19 does not have a direct impact on COVID-19 control. There is an influence of compliance on COVID-19 control, but no influence on prevention. There is no influence of COVID-19 control on prevention.